Succession mortis causa - Castellanos Ruiz, Esperanza (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The erga omnes nature of European Regulation 650/2012 and the primacy of EU Law over the domestic law of the Member States implies that the Spanish authorities, to determine what is applicable to the succession mortis causa, will apply the conflict rules contained in the European Regulation 650/2012 and not art. 9.8 CC. The art. 9.8 CC is currently only applicable to cases of interregional law, to succession cases relating to the succession of people who have died before August 17, 2015, and to the solution of the applicable inheritance law when Spanish Law is the Lex successionis. Its scope, therefore, has been greatly reduced in favor of European conflictual inheritance law, even in the determination of the specific applicable Spanish material inheritance law. Based on this premise, art is studied. 9.8 Cc. of the Spanish Preliminary Title, which, although in a subsidiary manner, is still in force.